PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA GURU SMPN 2 BANGKINANG KOTA - Yulizar Yulizar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This research was conducted at teachers of SMPN 2 Bangkinang Kota. The purpose of this study is to determine the effect of education and training on teachers’ performance at SMPN 2 Bangkinang Kota. The population in this study is all teachers of SMPN 2 Bangkinang City, with a sample of 64 respondents. The analysis technique used is multiple linear regression and hypothesis test. Partial research results obtained t count the education variable (X1) of 7603 with a significance of 0.000, it can be concluded that there is a significant influence of education variables on teachers’ performance at SMPN 2 Bangkinang Kota. Obtained t arithmetic training variables of 4.906 with a significance of 0.000, it can be concluded that there is a significant influence of training variables on teachers’ performance at SMPN 2 Bangkinang Kota. Based on simultaneous test that is obtained by significance value equal to 0.000, this number